Anxiety and depression among children and young people involved in family justice court proceedings: longitudinal national data linkage study - Lucy Jane Griffiths; Joanna Mcgregor; Theodora Pouliou; Rhodri D. Johnson; Karen Broadhurst; Linda Cusworth; Laura North; David V. Ford; Ann John (BJPsych Open, 2022)
Background Little is known about mental health problems of children and young people (CYP) involved with public and private law family court proceedings, and how these CYP fare compared to those not involved in these significant disruptions to family life.